Lobate Lac Scale, Paratachardina lobata lobata (Chamberlin) (Hemiptera: Sternorrhyncha: Coccoidea: Kerriidae) - F. W. Howard; Robert Pemberton; Avas Hamon; Greg S. Hodges; Bryan Steinberg; Catharine M. Mannion; David McLean; Jeanette Wofford (EDIS, 2005)
A species of scale insect new to Florida is potentially one of the most devastating pests of trees and shrubs in the state's history. The lobate lac scale, Paratachardina lobata lobata (Chamberlin) (Hemiptera: Sternorrhyncha: Coccoidea: Kerriidae), a scale insect native to India and Sri Lanka, was found for the first time in Florida in August 1999 by personnel of the Florida Department of Agriculture and Consumer Services, Division of Plant Industry (DPI) (Hamon 2001). This document is EENY-276, one of a series of the Department of Entomology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date printed: November 2002. Revised: May 2004.